Critical control points and critical limits for industrial scale Halal poultry meat production - Rahman, Mohammad Tariqur; Shahdan, Intan Azura (2014)
Government and non-government organizations in different countries are involved in certification of the halal (Arabic: lawful) status of products. Criteria to label a product as halal may vary depending on the predominant schools of thought of a country or nation. For instance, while water bath stunning before slaughtering is considered permissible in some countries for halal poultry meat production, others reject pre-slaughtering stunning. At the same time, to meet high demand of halal meat market, halal poultry meat production required adoption of automation and mechanical devices at different steps during slaughtering. The halal status of the food depends on the fundamental guidelines derived from the Qur’an and Hadith (the saying and living examples of Prophet Muhammad, peace be upon him). However, variations in the interpretation of these guidelines exist, making it difficult to have one universal halal standard which is acceptable for all Muslims all over the world. Despite the variations, it is possible to outline a systematic approach highlighting the critical points that need to be monitored and controlled for halal poultry meat production. We have proposed Halal Critical Control Point (HCCP) to ensure systematic production and evaluation of the halal poultry meat, from farm to table. Critical control points (CCP) are defined as the events or steps during the processing, compromise of which may render the end product as haram or shubhah. Based on the Qur’an, the Hadith, field survey and interviews with several officers of the religious councils, seven CCP were proposed. Critical limits (CL) are proposed for each CCP, either based on the field survey, experiments or existing empirical evidence. The CL for CCP1 (rearing) focus on HCCP compliant poultry feed ingredients and the genetic makeup of the chickens to be slaughtered. The CL for CCP2 (lairage) emphasises on minimum stress after transportation and before slaughtering process begins. The CL for CCP3 (immobilization) includes a gap of at least 5 sec to hang chickens onto the shackles and shackling time of less than a minute for every chicken before they are slaughtered. In countries which permit the use of water bath electrical stunning in poultry processing for halal meat production, the current to be applied for stunning must be defined according to the bodyweight and breed of the chickens and it must be shown that it does not cause the death of any of the chickens. As a part of the CL for CCP4 (tasmiyah and neck cutting), invocation of the name of Allah must be pronounced for every chicken or for each group of chickens being slaughtered. In CCP4 also, the recommended minimum time between neck cutting and scalding is 9 min. For CCP5 (scalding), counter-current water flow system must be used for scalding and the CL for the temperature is 50 to 60C. The CL for CCP6 (evisceration) is suggested as the rate of flowing water for washing eviscerated carcasses. Finally, the CL for CCP7 (deboning and packaging) emphasises zero adulteration of meat from other species, as well as maintenance of hygiene for the end products. As a conclusive remark, authors wish to declare that the proposed CCP and respective CL are not to be used as the global standard rather can be used as an example to derive required CCP and CL for a respective nation according to their Sharia law.